RESILIENSI PADA NARAPIDANA DITINJAU DARI SPIRITUALITAS DAN DUKUNGAN KELUARGA - Cahyani, Anggun Dwi; Nashori, Fuad (Psikis : Jurnal Psikologi Islami, 2024)
This study aimed to inquire about the prisoners' resilience in terms of spirituality and family support. The subjects of this study were 206 male prisoners of the "X" Correctional Institution in Yogyakarta. They were Muslim and aged between 18 and 60 years old. The data were collected in three scales: the Resilience scale (CD-RISC) developed by Connor-Davidson and adapted into Indonesian by Gina and Fitriani with a reliability value of 0.868, spirituality scale by Elkins et al which was adapted by Wahyuningsih into the Indonesian context with a reliability value of 0.915, and Family Support Scale (FFS) compiled by Uddin and Bhuiyan with a reliability value of 0.94. The writer analyzed the data by using multiple linear regression analysis and a partial correlation analysis. Its results revealed (1) a significant positive relationship between spirituality, family support, and resilience, (2) a significant positive relationship between spirituality and resilience, and (3) a significant positive relationship between family support and resilience. Therefore, there was a significant relationship between spirituality, family support, and the resilience of prisoners in correctional institutions.